SOCIETY PARTICIPATION IN DRAINAGE CONSTRUCTION AT PAWINDAN VILLAGE SUB-DISTRICT OF CIAMIS, DISTRICT OF CIAMIS - Enur Nurdin; Abdul Mutholib; Arie Budiawan (Faculty of Social And Political Science Universitas Galuh, 2021)
Based on the observation, it is known that drainage in Pawindan village sub-district of Ciamis, district of Ciamis has not been implemented properly, due to the level of societyâ€s participation in this construction still needs to be improved. Methodology of this research used descriptive analysis. Result of the research showed that society participation in drainage construction was not optimal regarding four kinds of activities, this case can be seen from the lack of society participation in deliberations to plan making decision at both the musrenbangdus and musrenbangdes, besides that, there is still a lack of society participation in the implementation of construction, so that the level of society cooperation is still lacking, another problem is related to the lack of society participation in the evaluation and monitoring of development results so that the society does not provide various inputs to the headman in the implementation of development. The obstacles encountered include the difficulty of involving the society in the deliberations to plan decision-making at the musrenbangdus and musrenbangdes, besides that it is still difficult to increase society participation in the implementation of development so that the cooperation is still lacking. The efforts that made to overcome obstacles to increase society in drainage construction are carried out by involving the society in deliberations to plan making decision at the musrenbangdus and musrenbangdes by inviting the society to attend the deliberation, besides inviting the society to participate in the implementation development through society cooperation activities.